On-Chip Clocking Scheme for Nanomagnet QCA - Alam, Mohmmad T.; Niemier, Michael; Porod, Wolfgang; Hu, Sharon; Putney, Michael; De Angelis, Jarett; Bernstein, Gary H. (2007 65th Annual Device Research Conference, 2007)
Quantum-dot Cellular Automata (QCA) has been demonstrated using aluminum tunnel junction single-electron transistor technology at mK temperatures, and molecular QCA is under development for operation at room temperature (RT). All of the basic building blocks needed for QCA have been experimentally demonstrated. Our work on nanomagnet-based QCA (NMQCA) holds the most promise for achieving viable RT operation in the near term. One requirement of the QCA architecture is low-power clock structures, which is the subject of this paper.